FINANCIAL BEHAVIOUR MEDIATING THE RELATIONSHIP BETWEEN FINANCIAL LITERACY, FINANCIAL ATTITUDES, FINTECH, AND STUDENTS’ INVESTMENT INTEREST - Sendilla Prisaura; Hamdani; Humairoh; Dhea Zatira (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2026)
The ongoing expansion of financial technology along with the relatively low level of financial literacy among students, emphasizes the need to better understand the factors that shape their investment interest. The purpose of this study is to examine how much financial behavior influences students' interest in investing by acting as a mediating variable in the link between financial literacy, financial attitudes, and the usage of fintech. A quantitative research design was adopted by administering a survey to 230 students in Tangerang Regency. SEM-PLS with SmartPLS 4 was used to analyze the data in order to look at indirect as well as direct correlations between the variables. The findings demonstrate that students' financial behavior is positively and significantly impacted by financial knowledge, financial attitudes, and fintech usage. Furthermore, financial behaviour also has a positive and significant impact on investment interest. However, financial literacy, financial attitudes, and fintech usage do not directly affect investment interest, indicating that financial behaviour fully mediates these relationships. this research emphasizes the importance of financial behaviour as the main mechanism that connects these factors to students’ investment interest, while also providing practical implications for enhancing financial education and fintech-based financial strategies.